Geotagged Application for Durian Trees using Aerial Imagery and Vegetation Indices Algorithm - Mohidem, N. A.; Jeya Kumaran, V.; Ab Rahman, M. I.; Che’Ya, N. N.; Rosle, R.; Fazlil Ilahi, W. F.; Hock, O. C.; Mat Su, A. S.; Ping, T. N.; Izan, S (Farm Machinery Industrial Research Corp, 2024)
Volume 52, Issue 03, December, 2021